From Charity to Climate Justice: 60 Years of Brazil's Fraternity Campaign in the Liturgical Public Sphere - Yamaguchi, João Akio Ribeiro (International journal of Latin American religions, 2025)
This article charts the historical evolution of Brazil’s Fraternity Campaign (1961-2025) through qualitative content analysis of official texts, posters, and hymns, supplemented by census data and synodal documents. It argues that the campaign's enduring see-judge-act framework has allowed the Brazilian Catholic Church to recalibrate its public engagement across three major inflexions: social charity under dictatorship, rights-based citizenship after redemocratisation, and integral ecology in the Francis pontificate. The ecological phase, inaugurated in 2011 and consolidated by the ecumenical "Casa Comum" cycle (2016), synchronises Lenten spirituality with national policymaking (most recently on sanitation, food security, and Amazonian land rights) while leveraging digital media to double parish participation. Although Catholic affiliation has fallen below 60 percent according to the 2022 Demographic Census by IBGE, the CF continues to operate as a liturgical public sphere that translates magisterial teaching into actionable civic agendas, positioning the Church as a key moral interlocutor ahead of COP-30 in Belém.